THE REPRESENTATION OF 21st CENTURY SKILLS IN AN INDONESIAN EFL TEXTBOOK - Rinekso, Aji Budi (LLT Journal: A Journal on Language and Language Teaching, 2021)
Textbooks play an important role in language teaching practices as the core source of knowledge. Meanwhile, the 21st century demands students having more advanced skills to solve the multifaceted and complex life situation. In fact, there are still limited studies evaluating textbooks based on the inclusion of 21st century skills. Looking at the gap, this study aimed to analyze the representation of 21st century skills in an Indonesian EFL textbook. A content analysis research design was applied in this study. The subject of the study was an EFL textbook used by grade 7 students. The results of the study revealed that there were 12 out of 15 of the 21st century skills presented in the textbook. The most dominant skills were communication and collaboration. The representation of the skills was done through some learning activities/tasks such as goal, input, procedure, teacher/learner role, pictures and notes. However, this textbook did not provide sufficient topics and materials about information, communication and technology (ICT). Therefore, it is suggested for further revision to include topics and materials about ICT.